Implementasi Nilai-Nilai Himatut Tasyri’ Haji Dalam Konteks Pembentukan Karakter Umat Muslim - Arifah, Sayyidah Fat Tahtul; Mukti, Gandhes Sasmitaning (Maliki Interdisciplinary Journal, 2025)
This research examines the values of Himayat Tashri’ Hajj in the character building of Muslims. Hajj is not only a ritual worship, but also contains values that support the strengthening of spirituality, morality, and social solidarity. Values such as patience, obedience, brotherhood, and simplicity are at the core of the messages of the Hajj Shari’ah. This study shows that the internalization of these values can shape the character of individual Muslims with noble character and strengthen harmony in social life. In conclusion, the values of Hajj play an important role in building the character of Muslims in accordance with the main objectives of Islamic law.